Continuity of traditions in the spiritual culture of turkic peoples in medieval states (according to Shajara-i Tarakime data) - Tashkaraуeva, A.M.; Abdykulova, G.; Smakhanovа, J.S. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The historical connections of Turkic peoples trace back to ancient times, extensively unfolding during the Middle Ages and subsequent eras. Throughout the entire medieval period, waves of people of Turkic origin came to lands that were once part of the Western empires. These tribes preserved a long history, traditions and skills on their way to their new homeland. They not only settled in their new lands, but also developed their culture, customs and skills in continuity with the world around them. This article is dedicated to the study of the interrelation of traditions in the spiritual culture of Turkic peoples based on oral historical traditions and legends in the work “Shajara-i-Tarakime”. We discuss the important aspects of forming the worldview foundations of Turkic-speaking peoples. Therefore, it is relevant to consider the problem of studying the ethnic identity of the early Turkic tribes in continuity with the study of ethno-political processes of the Middle Ages. The study of these historical events will not only help to more deeply reveal the issue of self-determination but will also allow for the identification of the formation of historical prerequisites for the beginning of economic, social, cultural, and political interaction of the Turkic peoples.
Ортағасырлық мемлекеттердегі түркі халықтарының рухани мәдениетіндегі дәстүрлердің сабақтастығы (Шаджар-и Таракиме деректері бойынша)
Преемственность традиций в духовной культуре тюркских народов в средневековых государствах (по данным Шаджара-и-Таракиме)
Keywords: Turkic peoples; Oghuz; Moghuls; Timurids; legend; myth; oral tradition; pedigree; genealogy